SISTEM KONTROL KENDARAAN BERBASIS IOT - Leonard Tambunan; Diki Dwi Putra (Jaringan Sistem Informasi Robotik-JSR, 2019)
Vehicle tracking system based on GPS (Global Positioning System) by using SMS gateway communication is a system where the position of a vehicle can be known with certainty. This tracking system uses Arduino Nano as a microcontroller, GPS module technology to determine the position of the vehicle and the SMS gateway device to communicate via Smartphone. With the Google maps application on the Smartphone, it is easy to track the position of the vehicle. The vehicle can be controlled by turning off and turning on remotely with the SMS gateway device via text message media on the Smartphone.